Przetrwanie czy upadłość? Klasyczne i nowoczesne metody prognozowania bankructwa przedsiębiorstw - Suraj-Sołtysiak, Magdalena; Sołtysiak, Mirosław (Survival or Bankruptcy? Classical and Modern Methods of Corporate Bankruptcy Prediction, 2006)
The article deals with a problem of financial condition's assessment in terms of bankruptcy prediction. The first part of the paper encompasses presentation of bankruptcy's notion from legal and economic point of view. Next, there is a short survey of bankruptcy prediction methods divided into classical and modem ones. The work presents both renowned and latest bankruptcy prediction models. Finally, current trends in scientific research on issue of bankruptcy and its prediction.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1116, s. 356-363